Facial contouring with parascapular free flap: A case series of 22 cases - Guru Dayal Singh Kalra; Ram Krishna Gupta (Indian Journal of Plastic Surgery)
Background: The facial asymmetry correction in complex craniofacial malformations presents a challenging problem for reconstructive surgeons. Progressive hemifacial atrophy (HFA) and hemifacial microsomia (HFM) can manifest in different grades of severity. Most patients require only soft-tissue augmentation. Free flaps are the best option for correction of severe facial soft-tissue deficiency. Materials and Methods: Twenty-two patients of HFM and HFA were included in this study from January 2006 to March 2009 in the Department of Plastic and Reconstructive Surgery, SMS Medical College and Hospital. In all cases, atrophy correction was done using de-epithelialised parascapular free flap with the de-epithelialised surface was placed under the skin. A small skin paddle was taken for monitoring. Results: All cases were reconstructed with de-epithelialised parascapular free flap. There was no flap loss in this series. Hematoma was noted in five cases. Debulking and removal of skin paddle were done in all cases after 6 months. Atrophy recurrence was not observed in any of the cases on follow-up. Conclusion: Contouring of face in cases of HMF and HFA is satisfactorily done with the parascapular free flap. It gives better cosmetic results with minimal donor site morbidity. Facial vessels are better recipient vessels for anastomosis. Keeping de-epithelialised surface of flap under the skin helped in preventing sagging.